FORMATION OF SOCIALLY ACCEPTABLE BEHAVIOUR OF CHILDREN WITH SPEECH DELAY - Tsymbalenko, Olena (PSYCHOLOGICAL JOURNAL, 2018)
The article describes and compares modern psycho-pedagogical correction therapies, creation of communication skills and socially important skills in children with speech delay, autistic syndrome disorder, and other developmental delays as they are described by modern scientific works. The article takes note of important common features in these therapies that are vital in any intervention. The article highlights the role of adults in psycho-pedagogical correctional therapy and development of communicative skills in children with speech delays. Establishing the adult as a leader and reference for a child with speech delay is key in a successful psycho-educational therapy. This leadership can only be established during emotionally important activities. This is an essential element of an activity that forms adult’s leadership in a relationship. Otherwise it will be next to impossible to build such a relationship. Teachers and parents must engage the child with speech delay in emotionally significant activities, they must become part of those activities. The adult with this emotional connection becomes the target and motivation for speaking. Establishing the leadership, engaging the child in emotionally significant interactions and the ability to receive praise from referential persons is the first and foremost motivation that supports the development of communicative skills in children with speech delays. It is vital for both parents and teachers to gain leadership and become the referential persons. Often it is the parents who are able to establish cooperation between various specialists that provide psyho-educational therapy for the child. United, specialists and parents are able to overcome the difficulties and help the child to integrate socially. Engaging the parents in the educational process of their children and teaching them the necessary skills has an incredible effect on the success of psyсho-educational therapy for children with speech delays.